2017
DOI: 10.4155/fmc-2017-0165
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanistic Antitumor Study of Myricanol 5-Fluorobenzyloxy Ether in Human Leukemic Cell Hl-60

Abstract: Aim:The aim of the study was to explore the growth inhibitory effect of myricanol 5-fluorobenzyloxy ether (5FEM) and the underlying mechanism in human leukemic cells HL-60. Materials & methods: 5FEM was obtained by chemical modification of myricanol with fluorobenzyloxy ether at the OH(5) position. The cytotoxicity, cell apoptosis, cell cycle and the expression of key apoptosis-related genes in HL-60 were evaluated. Results & conclusion: 5FEM can significantly inhibited growth of HL-60 cells, increased the G2/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In the anti-tumor screening of myricanol derivatives, we also used human lung fibroblast 1 (HLF1) as an evaluation of normal cytotoxicity. The results showed that 5FEM was found to have more antitumour activity and low toxicity to HLF1 than that of myricanol and other derivatives [20].…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In the anti-tumor screening of myricanol derivatives, we also used human lung fibroblast 1 (HLF1) as an evaluation of normal cytotoxicity. The results showed that 5FEM was found to have more antitumour activity and low toxicity to HLF1 than that of myricanol and other derivatives [20].…”
Section: Discussionmentioning
confidence: 94%
“…5-FEM (98.2% purity, batch number: 20170628) was prepared as previously described [20], Myricanol was added to acetone in a round-bottom flask, and stirred until dissolved. K 2 CO 3 was added, and then 4-fluorine benzyl bromide was added in the absence of light at room temperature.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
See 2 more Smart Citations